A plenary free individual traveler life cycle for assessment of adoption intelligent travel assistant - Noppadol Phaosathianphan (2020)
© 2020 The Authors This study aims to investigate antecedent variables and IT Processes being suitable factors for ultimately measuring and assessing feature values of an Intelligent Travel Assistant (ITA) related to the actual use of the Free Individual Traveler (FIT). Accordingly, the technology acceptance model (TAM) is extended with the essential factors of travel and tourism (i.e., Quality and Safety), and a plenary FIT life cycle (i.e., Pre-Trip, On-Route, On-Site, and Post-Trip). The data collection is gathered from 382 FITs in Thailand by the online questionnaire through famous social media, i.e., Facebook and Line. Hence, the collected data are analyzed statistically by PASW Statistics and SmartPLS. Therefore, the distinguished finding of this study is obtained from the useful assessment model, which is decided to usage for FITs and investment of ITA operators for travel and tourism firms.